2015
DOI: 10.1038/srep09301
|View full text |Cite
|
Sign up to set email alerts
|

Identification of proteins responsible for adriamycin resistance in breast cancer cells using proteomics analysis

Abstract: Chemoresistance is a poor prognostic factor in breast cancer and is a major obstacle to the successful treatment of patients receiving chemotherapy. However, the precise mechanism of resistance remains unclear. In this study, a pair of breast cancer cell lines, MCF-7 and its adriamycin-resistant counterpart MCF-7/ADR was used to examine resistance-dependent cellular responses and to identify potential therapeutic targets. We applied nanoflow liquid chromatography (nLC) and tandem mass tags (TmT) quantitative m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 57 publications
1
33
1
Order By: Relevance
“…Moreover, evidence suggested that elevated levels of NADPH and GSH, together with an active PPP, play an important role in MDR2930. Our results together with other recent studies3132 contradict the above-mentioned reports, showing that PPP enzymes are downregulated in MDR cells. These results are controversial since one of the roles of PPP is to provide reducing power to the GSH metabolism and high levels of GSH in tumors have been linked to the development of MDR33.…”
Section: Discussioncontrasting
confidence: 78%
“…Moreover, evidence suggested that elevated levels of NADPH and GSH, together with an active PPP, play an important role in MDR2930. Our results together with other recent studies3132 contradict the above-mentioned reports, showing that PPP enzymes are downregulated in MDR cells. These results are controversial since one of the roles of PPP is to provide reducing power to the GSH metabolism and high levels of GSH in tumors have been linked to the development of MDR33.…”
Section: Discussioncontrasting
confidence: 78%
“…NRF2-induced GCLM expression up-regulates GSH synthesis and associated Imatinib resistance in chronic leukaemia cells has been reported [24,177] . The enzymes involved in the pentose phosphate pathway (PPP) including glucose-6-phosphate dehydrogenase, isocitrate dehydrogenase 1, malic enzyme 1, transketolase isoform 1 and transaldolase 1 were found to be regulated by NRF2 [178][179][180][181] . Anticancer drug induced NRF2 hyperactivation transcriptionally activates these genes and facilitates PPP.…”
Section: Other Nrf2 Regulated Genes/proteinsmentioning
confidence: 99%
“…Some other genes, such as glucose-6-phosphate dehydrogenase (G6PD), isocitrate dehydrogenase 1 (IDH1) (Wang et al, 2015), malic enzyme 1 (ME1) (Cui et al, 2014), transketolase isoform 1 (TKT) and transaldolase 1 (TALDO1) (Basta et al, 2008) are also found to be regulated by NRF2 in human and mouse model (Chartoumpekis et al, 2015). All of them are involved in the pentose phosphate pathway (PPP) that provides energy for cell proliferation.…”
Section: Other Metabolism-related Genes Targeted By Nrf2 In Cancermentioning
confidence: 99%